Eterično olje prave sivke in lavandina - Matičič, Ana (Farmacevtski vestnik, 2023)
Lavender is a well-known Mediterranean plant, which includes common lavender (Lavandula angustifolia) and hybrid lavender or lavandin (Lavandula x intermedia). The essential oil of common lavender is used as a traditional herbal medicinal product for the relief of mental stress and exhaustion, and to aid sleep. On the market, it is often confused with lavandin oil, which differs significantly in its composition. In the present study, commercially available lavender and lavandin essential oils were analysed, their composition was determined using gas chromatography combined with mass spectrometry, and their antioxidant activity was evaluated using the DPPH assay. It was found that the key compounds for antioxidant activity are not the compounds present in higher concentrations in the samples, but ?-pinene, ß-pinene, ?-3-carene, hexyl butyrate, 7-epi-sesquitugene and ?-trans-bergamotene. Among the tested samples, the lavender from Bulgaria proved to be the most antioxidant active, while the lavandin Grosso showed the least activity. These results contribute to a better understanding of the use of these oils for therapeutic and cosmetic purposes and encourage further research on essential oils of different origins.
Keywords: Eterična olja; eterično olje; Lavandula angustifolia; Lavandula x intermedia; Sivka